Bottled mineral water as a potential source of antibiotic resistant bacteria - Falcone-Dias, Maria Fernanda [UNESP]; Vaz-Moreira, Ivone; Manaia, Celia M. (Pergamon-Elsevier B.V. Ltd, 2012)
The antibiotic resistance phenotypes of the cultivable bacteria present in nine batches of two Portuguese and one French brands of commercially available mineral waters were examined. Most of the 238 isolates recovered on R2A, Pseudomonas Isolation agar or on these culture media supplemented with amoxicillin or ciprofloxacin, were identified (based on 16S rRNA gene sequence analysis) as Proteobacteria of the divisions Beta, Gamma and Alpha. Bacteria resistant to more than three distinct classes of antibiotics were detected in all the batches of the three water brands in counts up to 10(2) CFU/ml. In the whole set of isolates, it was observed resistance against all the 22 antimicrobials tested (ATB, bio-Merieux and disc diffusion), with most of the bacteria showing resistance to three or more classes of antibiotics. Bacteria with the highest multi-resistance indices were members of the genera Variovorax, Bosea, Ralstonia, Curvibacter, Afipia and Pedobacter. Some of these bacteria are related with confirmed or suspected nosocomial agents. Presumable acquired resistance may be suggested by the observation of bacteria taxonomically related but isolated from different brands, exhibiting distinct antibiotic resistance profiles. Bottled mineral water was confirmed as a possible source of antibiotic resistant bacteria, with the potential to be transmitted to humans. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Antibiotic resistance; Drinking water; Mineral water